The ethics of COVID-19 vaccine allocation: Don't forget the trade-offs! - März, Julian; Molnar, Anett; Holm, Søren; Schlander, Michael (Public health ethics, 2022)
The issue of COVID-19 vaccine allocation is still highly controversial on the international as well as on the national level (particularly in many low- and middle-income countries), and policy-makers worldwide struggle in striking a fair balance between different ethical principles of vaccine allocation, in particular maximum benefit, reciprocity, social justice and equal respect. Any political decision that implements these principles comes at a cost in terms of loss of lives and of loss of life years that could potentially have been prevented by a different vaccination strategy. This article illustrates these trade-offs using quantitative analysis and shows how this approach can contribute to providing a rational and transparent grounding of political decisions on COVID-19 vaccine allocation.
Im Titel ist hinter "trade-offs" ein Ausrufezeichen
Gesehen am 30.01.2024